Varietal susceptibility and weed-control efficiency of fluazifop-p-butyl in soybean (Glycine max) - TIWARI, J P; KURCHANIA, S P; PARADKAR, N R; BHALLA, C S (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted dming the rainy season of 1991-92 and 1992-93 in split-plot design to study theeffect offluazifop-p-butyl on vruieties of soybean [Glycine max (L.) Merr.]. The application of fluazifop-p-butyl @ 0.25and 0.5 kg/ha post-emergence at 20 days after sowing effectively controlled the grass weeds, viz barnyard grass [Echinochloa crus-galli (L.) P. Beauv.], bermuda grass [Cynodon dactylon (L.) Pers.] and hairy crabgrass [Digitaria adscendens (H.B & K.)Henr.]. The broad-leaf weeds and sedges were found resistant. The soybean varieties 'JS 75-46', 'JS 72-44', 'JS 8021', 'Durga', 'JS 76-335' and 'JS 76-205' did not show any phytotoxic symptom. However, higher rate (0.5 kg/ha) of fluazifop-p-butyl led to norrowing of leaves, but did not affect the growth. The varietal differences in yield (1 647 - 2 151 kg/ha) were not significant. F1uazifop-p-buty1 treatments (1 872 - 1 934 kg/ha) and hand-weeding (2033 kg/ha) significantly increased the seed yield compared with the weedy control (1 509 kg/ha).